KEBERMAKNAAN HIDUP PADA LANSIA DI PANTI WREDA - Anindita Nova Ardhani; Yudi Kurniawan (UIN Sunan Kalijaga, 2020)
The aim of this study was to see the meaning of life in the elderly who live in the nursing home. The benefits that are expected to have in this research include theoretical benefits, which are expected to be a reference material for the development of developmental psychology, especially psychogerontology and practical benefits to be a reference material for psychologists, therapists, counselors, assistants, and readers in an effort to increase the meaning of life. in the elderly in general and in the elderly who live in nursing homes in particular. The subject criteria for the study were the elderly who were still able to communicate with and in good general condition. These criteria are determined on the basis of consideration because this study was conducted using interviews as a method of data collection. The results of this study indicate that the elderly who live in nursing homes have a good life meaning.Keywords: nursing homes, parents, the meaning of life,